Perencanaan Sistem Jaringan Air Bersih Pada Daerah Juata Kecamatan Tarakan Utara - Rosmalia Handayani; Kiky Fauzi Nuzulika (Borneo Engineering : Jurnal Teknik Sipil, 2022)
The development of Tarakan City, there is an increase in terms of growth, activity, and the number of population which is always closely related to the clean water, causing an increase in the need for clean water. The low level of clean water services for the North Tarakan area, which is 54,04%. This study aims to determine the projected need for clean water until 2030. Planning for the provision of clean water in the District of North Tarakan until 2030 with the help of the WaterCAD v8i program is in accordance with population growth and clean water needs. The results of the calculation of the average water demand in 2030 amounted to 51,8676 liters / second, the maximum daily requirement of 59,6477 liters / second, the total water demand obtained at peak hours in 2030 was 80,9135 liters / second. From the simulation results with the help of the WaterCAD V8i program that the piping network system can work well. This is based on the pressure at the junction 0,60-7,96 atm, Headloss Gradient 0-12,27 m / km, and the speed of 0,11-1,23 m / sec. These results are in accordance with planning requirements